Membranous glomerulonephritis: role of retinol-binding protein in monitoring and prognostication - Maifata, Sadiq Muazu; Abd Ghani, Fauzah; Hod, Rafidah; Zakaria, Nor Fadhlina (MDPI, 2021)
Initially, retinol-binding protein (RBP), was thought to be a biomarker for proximal convoluted tubule dysfunction could be important in chronic kidney diseases (CKD). Membranous glomerulonephritis (MGN) is an important cause of CKD and end-stage renal disease (ESRD). Therefore, monitoring MGN patients using urinary RBP is important in effective treatment decision making and prognostication of MGN patients. Enzyme-linked immunosorbent assay (ELISA) technique was used to detect the RBP in the urine samples of 69 MGN patients comprising 47 primary and 22 secondary MGN, at the end of the follow-up period. The test for the urinary biomarker gave the following results: urinary RBP was detected in 27 (39.1%) and 6 (8.7%) of the primary and secondary MGN patients, respectively. The correlation analysis demonstrated a significant relationship between urinary RBP and renal function test parameters, in addition to a logistic regression analysis that proved urinary RBP as a prognostic non-invasive biomarker for primary MGN. Therefore, urinary RBP could be employed to monitor and provide effective prognosis and early treatment decisions in primary MGN.